ANALISIS KEMAMPUAN LITERASI MATEMATIS SISWA DALAM PENYELESAIAN SOAL PISA DITINJAU DARI GENDER - Aditya Setiawan; Siti Inganah; Siti Khoiruli Ummah (Universitas Muhammadiyah Semarang, 2019)
This study aimed to describe the ability of mathematical literacy’s male and female students in Grade VIII. Based on the results of the interview, teacher accustomed to adopt problems of the textbook and national exams. Mathematical literacy was important to resolve the real problem in the form of the story matter. The research method used descriptive research. Data obtained from the mathematical literacy ability tests and interviews. The data was analyzed by observing the stages of how students in solving a problem were given. The results of the study were male students mathematical literacy ability was good enough in the settlement of the question of tests and reasonable when interviewed. Female students already have pretty good abilities in tests but were still lacking in reasoning and confident at interview sessions. Both of the students were men and women overall have been able to meet the competencies of mathematical literacy